Electrically triggered spin reversal and precise control of spin polarization for electron transport at the single-molecule level - Zeng, Hong-Li; Zhao, Hong-Ru; Guo, Yan-Dong; Zhao, Xue; Wang, Yu-Hao; Lin, Li-Yan; Ma, Ao; Yan, Xiao-Hong (Journal of applied physics, 2023)
Different from conventional ferromagnetic methods, producing a spin-polarized current through electrical ways in spintronic devices can greatly increase operating speed, reduce power consumption, and improve device integration. Inspired by recent experimental progress on the synthesis of a heptauthrene molecule, we investigate its spin-dependent transport contacted with Au electrodes through first-principles calculations. By applying a gate voltage, the transmission can be switched between completely spin-up and spin-down polarized states, achieving an electrically controlled dual-spin filter. Furthermore, a fine tuning on the spin polarization, between 100% and −100%, can also be realized, where the transport with any ratio of spin-up to spin-down electron quantities can be realized beyond the traditional devices. The peculiar transmission spectra and their shift are found to play crucial roles, where transmission peaks distribute on both sides of the Fermi level with opposite spin components. Such a spin-polarization modulating effect is found to be robust to the molecule-electrode contacting site, indicating it is an intrinsic feature of such systems. Moreover, the dimension of the device is at the single-molecule level, suggesting great application potential.